Uji Beberapa Zat Pengatur Tumbuh (ZPT) Alami untuk Perbanyakan Vegetatif Bonggol Pisang (Musa paradisiaca L.) Varietas Kepok Tanjung - Febmita, Elna; Putri, Santi Diana (UNIVERSITAS LABUHANBATU, 2023)
In the propagation of Kepok Tanjung Bananas, many use natural vegetative propagation, so that the seeds obtained are in small quantities and require a long time, while artificial vegetative propagation has advantages, among others, in a short time it can produce large amounts of uniform seeds. Propagation of seedlings from weevils can take advantage of the remaining felled stump so that the cost is relatively cheap. By administering some natural Growth Regulatory Substances (PGR) can affect the success of vegetative propagation using weevils. The role of PGR, among others, is to regulate the speed of growth and integrate plant tissues to form a plant. The research objective was to obtain the best shoot growth from the vegetative propagation of the banana weevil (Musa paradisiaca L.) kepok tanjung variety by administering some natural Growth Regulatory Substances (PGR). This study used an experimental method using a completely randomized design (CRD), with treatments namely B0: Control; B1: bamboo shoot extract; B2: shallot extract; B3: coconut water. Parameters observed were the age of shoot emergence, number of shoots, shoot length, age of transplanting or transplanting. The results of the test of several natural Growth Regulatory Substances (PGR) for vegetative propagation of the banana weevil (Musa paradisiaca L.) of the Kepok Tanjung variety that have been carried out can be concluded that the application of several natural PGR, coconut water provides higher shoot growth with a total of 5 shoots, shoot length was 92.5 cm, number of leaves was 2.60 and the age of transplanting was 39.8 DAP, while PGR of bamboo shoots could accelerate the age of shoot emergence on day 28.8.Â Keywords:Banana Weevil, Vegetative, Natural PGR